Do sexual calls in female black capuchin monkeys (Sapajus nigritus) vary with fertility? An acoustic analysis. Issue 9 (8th October 2018) - Bernaldo de Quirós, Ester; Wheeler, Brandon C.; Hammerschmidt, Kurt; Heistermann, Michael; Tiddi, Barbara
Abstract : Females across a range of animal taxa produce vocalizations and signals uniquely associated with periods of mating. While such signals may ultimately function to increase female attractivity to males, conflicting findings challenge the extent to which these signals co‐vary in accordance with the probability of conception. Female black capuchin monkeys ( Sapajus nigritus ) display an elaborate repertoire of both vocal and visual components as part of their socio‐sexual behavior, and previous analyses have shown that the rates of production of visual, but not vocal, components provide graded information on female ovulation. It remains possible, however, that the acoustic parameters of these sexual calls, rather than their rate of productions, co‐vary with female fertility. To test this, we analyzed structural and temporal call parameters from estrous calls and post‐copulatory calls recorded over five consecutive mating seasons in 12 sexually mature females at Iguazú National Park, Argentina. Calls given during the fertile phase of the female ovarian cycle were compared with those given during the non‐fertile phase, as determined by profiles of female reproductive hormones. Similarly, within the fertile phase, we tested whether temporal or spectral acoustic parameters of calls gradually change with the approach of ovulation. We did not find any significant relationship between call parameters and the two measures of female fertility in either female estrous calls or post‐copulatory calls. However, some differences between pre‐ and post‐copulatory calls were apparent. Overall, our results indicate that sexual calls in black capuchin females do not provide precise information about the timing of ovulation, but may allow listeners to make probabilistic inferences about whether copulations have taken place. This, combined with previous findings, suggests that females in our study may use signals in different modalities to convey information about their fertility and sexual behavior with varying degrees of precision. Abstract : This study tested if the acoustic structure of sexual calls in wild black capuchin females varies with fertility. Results indicate that sexual calls in this species do not provide graded information about the timing of ovulation.